L’expertise sportive : les femmes mises en échec - Marilou St-Pierre (Communiquer)
The sport/media complex has been accompanied by a complexification of the sport media market. In order to distinguish themselves from the competition, sports media have made more space for experts in their pages and schedules. But despite multiplication these expert voices, including analysts, descriptors and chroniclers, women remain largely absent from these positions. Using Collins and Evans’ expertise typology to explore the descriptions of these experts made by five Quebecois French-language media, I discovered that the expert’s status is not reserved to former pro athletes. If it had been the case, women would have been left outside the expert’s position. Interviews with women sports reporters and analysts allowed me to suggest that the absence of women’s experts is largely based on management bias, without any link to the desirable qualities of experts.